Problem Kata ‘Tinggal’ dalam 2 Yohanes Ayat 2 Versi TB 2: μένουσαν, ἐνοικοῦσαν, atau οὖσαν? - Prabowo, Paulus Dimas; Rumbekwan, George; Sinaga, Donna Crosnoy (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The word 'remain' in 2 John verse 2 TB 2 version contains problems. First, there are three Greek variants of this word, namely μένουσαν, ἐνοικοῦσαν, and οὖσαν. Second, each variant has a certain theological emphasis based on the chosen understanding. Third, A Textual Commentary on The Greek New Testament does not detect and identify the existence of these three variants. This article was written to achieve several goals: first, to review each variant to discover its theological meaning; second, comparing the three variants to determine which possible variation is closest to the original text of the Bible. Through a text critical approach supported by grammatical-syntactic analysis, the results obtained are that the first variant, namely μένουσαν (menousan) has the strongest position with a lot of support from a cultural, contextual and theological perspective. The habitual aspect can be seen in John's tendency to use the word μένω (meno) in his writings, with a total of 67 uses or 56.8% of 118 occurrences in the New Testament, even 31 ancient manuscripts including the two Great Uncial Codexes (Sinaiticus and Vaticanus) and the Vulgate choose the first version. The contextual aspect can be seen in verse 2b, namely μεθ᾽ ἡμῶν ἔσται εἰς τὸν αἰῶνα which emphasizes time and from the appearance of the word μένω in verse 9 which shows harmony. The theological aspect can be seen in emphasizing the meaning of the permanence of truth (aletheia) based on lexical analysis, including its use in secular ancient Greek literature, and contextual analysis, namely the appearance of τὸν αἰῶνα (ton aiona) in verse 2b and προάγων (proagon), so that John's message is that the congregation persists in the true teaching, without leaving it.